Nuances of Edutainment in Mushaf: Analysis of Learning Methods in Edutainment in Indonesian Al-Qur'an Mushaf - Fatchiatuzahro Fatchiatuzahro (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
In this research, the relevance of the innovative use of edutainment in the manuscripts of the Al-Qur'an is explained. Apart from strengthening the existence of the Al-Qur'an manuscripts, the addition of this innovation is in line with the concept of contemporary education, namely anthropocentric. In terms of analysis, this research is qualitative-exploratory with sources from 15 trendy manuscripts. The approach in this research is philosophical-speculative to always present the relevance of edutainment in the manuscripts of the Al-Qur'an. This research concludes that the relevance of publishing specific editions of manuscripts with the concept of edutainment can accommodate the cognitive, physiological, and psychological needs of readers in terms of several learning theories, such as cognitivism, behaviorism, humanism, cybernetics, and multiple intelligences, as well as learning methods. Quantum learning, active learning, multiple intelligences, accelerated learning.